Factors Affecting Profit Quality in Non-Bank Financial Sector Companies - Alfina, Alfina Maharani; Wiwik, Wiwik Utami (International Journal of Indonesian Business Review, 2024)
Purpose –PeThis study aims to analyze the effect of profit growth, capital structure, investment opportunity set, and audit committee on profit quality in non-bank financial sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. Methodology/approach –This research is a causal research with a quantitative approach. Secondary data in this study were obtained from the Indonesia Stock Exchange (IDX) or the company's official website. The sampling method used the purposive sampling method and obtained 45 companies with 3 years of research. The analysis technique used is multiple linear regression analysis with the IBM SPSS version 25 application. Findings –The results of this study indicate that profit growth has no effect on profit quality, capital structure has a significant positive effect on profit quality, investment opportunity set has a significant negative effect on profit quality, and the audit committee has no effect on profit quality. Novelty/value –This study proves that the investment opportunity set is a factor that drives an increase in the quality of company profits as proxied by the Market to Book Value of Assets Ratio.